BAHASA GAUL SEBAGAI MEDIA KOMUNIKASI BUDAYA DI ZAMAN MILENIAL - Wahyu Mulyani; Sarujin Sarujin; Ari Cahya Puspitaningrum (SEMIOTIKA: Jurnal Ilmu Sastra dan Linguistik, 2022)
This study aims to discuss (1) adolescent slang in the form of abbreviations in the WhatsApp(WA) group of national-level short story writing competitions, (2) youth slang in the form ofwords in the WA group, and (3) slang as a medium of cultural communication in the millennialera. The research method uses qualitative methods. The research data were taken from two WAgroups in the national-level short story writing competition. Data collection techniques usinglistening and tapping techniques. The time used for data collection is half a year, from July2021 to December 2021. The results show ten forms of abbreviations and fifteen forms ofwords. Ten forms of abbreviations used by teenagers in chatting in the WA group of nationallevel short story writing competitions have variety, including abbreviations in English andIndonesian. The fifteen-word forms used by teenagers in chatting in the group also varied; ninewords came from English, six words came from Indonesian, there were variations inIndonesian words whose spellings were reversed (from the middle and behind), and There weretwo Jakarta dialect words. These findings represent adolescent self-identity. Communicationin the form of chatting is a youth culture, so there is a national-level short story writingcompetition in the WA group, which feels that teenagers tend to use slang. The number ofEnglish teenagers use in cultural communication shows that they want to be seen as modernand cool. By being looked at like that, teenagers feel happy and proud because they feel theyare not out of date. The findings from the study show that millennial youth have creativity incommunicating through abbreviations and variations of English to represent the context ofcontemporary culture that is modern, cool, and proud.